2021
DOI: 10.3389/fendo.2021.730947
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Molecular Characterization of Adrenals and Adrenal Rest Affected by Congenital Adrenal Hyperplasia

Abstract: IntroductionAdrenocortical hyperplasia and adrenal rest tumor (ART) formation are common in congenital adrenal hyperplasia (CAH). Although driven by excessive corticotropin, much is unknown regarding the morphology and transformation of these tissues. Our study objective was to characterize CAH-affected adrenals and ART and compare with control adrenal and gonadal tissues.Patients/MethodsCAH adrenals, ART and control tissues were analyzed by histology, immunohistochemistry, and transcriptome sequencing. We inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Our data support the theory introduced in 1950 that adrenal tissue has common precursor progenitor cells for both hematopoietic and mesenchymal lineages, especially adipose and immune cells [ 14 ]. We previously reported a lack of zonation [ 15 ] and lymphocytic infiltration [ 16 ] in the adrenals of patients with classic CAH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data support the theory introduced in 1950 that adrenal tissue has common precursor progenitor cells for both hematopoietic and mesenchymal lineages, especially adipose and immune cells [ 14 ]. We previously reported a lack of zonation [ 15 ] and lymphocytic infiltration [ 16 ] in the adrenals of patients with classic CAH.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple tissue sections with a thickness 5 µm from formalin-fixed paraffin-embedded (FFPE) tissue blocks of CAH adrenal, normal adrenal, normal adipose tissue, and tumor myelolipoma tissue sections were mounted on Superfrost plus slides (Erie Scientific, Ramsey, MN, USA) and hematoxylin and eosin (H&E) staining was performed on tissue sections from CAH adrenal, normal adrenal, and adrenal myelolipoma, as previously described [ 16 ]. Histopathological assessment of inflammation and expression of inflammatory markers was performed using prediluted antibodies as markers (Roche Tissue Diagnostics, Marlborough, MA, USA), CD3 (T lymphocyte-specific) (790–4341: clone 2GV6), CD20 (B-lymphocyte-specific) (760–2531: clone L26), and CD68 (macrophage/monocyte histiocyte-specific (790–2931: clone KP-1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been shown that 11β-hydroxysteroid dehydrogenase types 1 and 2 are expressed in testicular Leydig and ovarian theca cells ( 15 ), our findings contradict the idea that gonadal 11-KT production significantly contributes to the systemic pool in females because CYP11B1 is usually only expressed in negligible amounts in the gonads ( 23 ). An exception to this are patients with CAH in which aberrant adrenal tissue can be found within the testicles or ovaries ( 24 , 25 ). The idea that 11-KT is produced in peripheral tissue from 11-OHA4 produced in the adrenal is supported by the observation that 11-KT levels did not differ between the sampling sites, considering the significantly higher 11-OHA4 levels in the adrenal vein samples, especially.…”
Section: Discussionmentioning
confidence: 99%
“…Histological and biochemical profiles highlight zone-specific alterations in the adrenal cortex in CAH. For example, immunostaining of CAH-affected adrenal glands shows a strong presence of zona reticularis enzyme CYB5A compared with other zones 20 , 21 (Fig. 2 ).…”
Section: Pathophysiologymentioning
confidence: 94%